2009
DOI: 10.1121/1.3075551
|View full text |Cite
|
Sign up to set email alerts
|

An in situ calibration for hearing thresholds

Abstract: Quantifying how the sound delivered to the ear canal relates to hearing threshold has historically relied on acoustic calibration in physical assemblies with an input impedance intended to match the human ear (e.g., a Zwislocki coupler). The variation in the input impedance of the human ear makes such a method of calibration questionable. It is preferable to calibrate the acoustic signal in each ear individually. By using a calibrated sound source and microphone, the acoustic input impedance of the ear can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 22 publications
1
43
0
3
Order By: Relevance
“…2, for which the maximum L FE was 6 dB at the 75th percentile. Experimental results from Withnell et al (2009) are also generally consistent with Keefe and Abdala (2007) and the present results. Differences between studies emphasize the importance of individual variability in ear-canal acoustics, including variability in the depth of insertion of the probe.…”
Section: B Acoustic Transfer-function Measurementssupporting
confidence: 81%
See 1 more Smart Citation
“…2, for which the maximum L FE was 6 dB at the 75th percentile. Experimental results from Withnell et al (2009) are also generally consistent with Keefe and Abdala (2007) and the present results. Differences between studies emphasize the importance of individual variability in ear-canal acoustics, including variability in the depth of insertion of the probe.…”
Section: B Acoustic Transfer-function Measurementssupporting
confidence: 81%
“…Scheperle et al (2008) reported that an in-theear stimulus calibration based on forward pressure level or intensity level provided more consistent DPOAE measurements between 2 and 8 kHz compared to a calibration based on total pressure. Based on analyses of measurements between 0.25 and 6 kHz, Withnell et al (2009) proposed that either forward pressure or the fraction of total pressure at the tympanic membrane that is not reflected at the tympanic membrane be used to specify behavioral hearing threshold rather than total pressure. Calibrating the ear-canal stimulus according to forward pressure level has also been suggested for hearing-aid applications using probe-microphone measurements in the ear canal Lewis et al, 2009) and compared with calibrations using total pressure level in DPOAE measurements (Burke et al, 2010).…”
Section: Constant Stimulus-level Proceduresmentioning
confidence: 99%
“…Data is presented from six subjects, four female and two male. The method for data collection has been described previously (see Withnell et al 2009). Briefly, signal generation and data acquisition was computer-controlled using the Mimosa HearID system with version R4 software module (www.mimosaacoustics.com).…”
Section: Subjects and Data Collectionmentioning
confidence: 99%
“…Data for this study was drawn from a larger data set obtained as part of an NIH-funded Small Business Innovation Research grant. The method for data collection has been described previously, see Withnell et al [11]. This study was completed with the approval of the Indiana University Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%